Stunting Literacy Strategy for the Community using a Website-Based Media Platform - Budy Santoso; Yuliana Retnowati; Abubakar Sidik Katili; Margaretha Solang; Paulus Pangalo; Indra Domili; Novian Swasono Hadi (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Stunting in toddlers is still a problem in Indonesia. Kalimas Village is one of the stunting village loci with a prevalence rate of 14.7 percent in Pohuwato District. Low community knowledge related to stunting and variations in complementary foods for children is one of the triggers for the high stunting rate in this village. Therefore, it is necessary to increase understanding related to handling stunting and its prevention. One strategy to increase understanding is to provide learning contents to improve stunting literacy through the development of a website that contains comprehensive stunting education articles and videos. In addition, educational videos on processing local food into additional food that has nutritional value for stunted children are also provided. With this educational website, the village can also publicize the potential of the village so that it can develop the existing village potential.